Developing an Intelligent PostGIS Database to Support Accessibility Tools for Urban Pedestrians - Daniel Sinkonde; Leonard Mselle; Nima Shidende; Sara Comai; Matteo Matteucci (Urban Science, 2018)
People with mobility impairment must travel through cities with extra care. An intelligent database of Maps for Easy Paths (MEP) project for storing and retrieving accessibility information about a particular path by using PostGIS may enable the public to enjoy the privilege of the technology that alleviates the problem of city accessibility through the Web or, more recently, through smartphones/tablet applications. The methods and techniques for intelligent database to storeand retrieve accessibility information by using a relational intelligent PostGIS database are described. The conceptual data model is designed for an intelligent database (PostGIS). Users will be able to actively participate in the process of taking pictures of obstacles, uploading them to the MEP server and giving some comments on the attributes of the picture of the barrier. The resulting data will help others to locate and evaluate paths. This paper presents the conceptual data model design as well as a review of features of the data of the existing systems. Therefore, the novelty of this approach lies in developing an intelligent database for the enrichment of geographical maps with information about the accessibility of urban pedestrian areas for people with mobility problems.